Mechanism of ice nucleation in liquid water on alkali feldspars. (7th April 2022) - Keinert, Alice; Deck, Kathrin; Gaedeke, Tilia; Leisner, Thomas; Kiselev, Alexei A.
Abstract : Patches of (100) crystalline surface in perthite feldspars are confirmed to induce ice nucleation in liquid water and from water vapor. Abstract : Crystallization of supercooled liquid water in most natural environments starts with heterogeneous nucleation of ice induced by a nucleation site. Mineral surfaces, which form the majority of aqueous interfaces in Earth's ecosystem, possess a plethora of surface morphological and chemical features that can serve as ice nucleation sites. The nature of surface sites responsible for ice nucleation from supersaturated water vapor have been recently identified for alkali feldspar, a family of rock-building minerals constituting 60% of the Earth's crust. It was demonstrated that ice preferentially forms upon the patches of crystalline surface with (100) orientation, exposed in the surface defects such as cracks, pores, and pits arising due to chemically induced stress and further enhanced by hydrothermal alterations of natural feldspars. However, whether the same sites were responsible for nucleation from liquid water, remained to be shown. Here, we investigate the mechanism of heterogeneous ice nucleation in a layer of aqueous sucrose solution on top of thin sections of feldspar prepared along the (010) crystalline plane. We observe a preferential orientation of ice crystals defined by an epitaxial relationship between feldspar and ice, with ice crystals growing on the crystalline surfaces of feldspar with (100) orientation. We thus conclude that the ice nucleating sites active in deposition freezing mode are also active in the immersion freezing regime. This conclusion is further supported by the enhancement of ice nucleation active site density observed for the thin sections of feldspar prepared sub-parallel to the (100) plane as compared to sections prepared along (010) and (001) crystallographic orientations.